2010
DOI: 10.1159/000320594
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of Par-4 Protects Human Renal Proximal Tubule Cells from Apoptosis Induced by Oxidative Stress

Abstract: Background: Oxidative stress is an important inducer of cell apoptosis and plays a key role in the development of renal inflammation. The prostate apoptosis response factor-4 (Par-4) gene was originally identified in prostate cells undergoing apoptosis. Subsequently, Par-4 was found to possess potent pro-apoptotic activity in various cellular systems. However, it remains unclear whether Par-4 is involved in oxidant injury of renal tubular epithelial cells. Aims: To determine the role of Par-4 in renal proximal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 72 publications
(60 reference statements)
0
2
0
Order By: Relevance
“…As for Gdh, starvation decreased hepatic mRNA levels of Usf2 in the liver of S. aurata. In this regard, it was previously reported that high glucose levels upregulate Usf2 expression in human-derived HK-2 cells and primary rat mesangial cells (Shi et al 2008, Visavadiya et al 2011, Wang 2015. Therefore, low levels of glycemya associated to long-term starvation may be critical to downregulate Usf2 expression, which in turn may lead to decreased Gdh mRNA levels in the liver of S. aurata.…”
Section: Figurementioning
confidence: 94%
“…As for Gdh, starvation decreased hepatic mRNA levels of Usf2 in the liver of S. aurata. In this regard, it was previously reported that high glucose levels upregulate Usf2 expression in human-derived HK-2 cells and primary rat mesangial cells (Shi et al 2008, Visavadiya et al 2011, Wang 2015. Therefore, low levels of glycemya associated to long-term starvation may be critical to downregulate Usf2 expression, which in turn may lead to decreased Gdh mRNA levels in the liver of S. aurata.…”
Section: Figurementioning
confidence: 94%
“…Conversely, IGF-1 activated SphK1 and this effect was mediated by ERK/PI3K/Akt in ECs [ 247 ]. Furthermore, H 2 O 2 downregulated VEGF via inhibition of theh PI3K/Akt pathway, leading to apoptosis in RTCs [ 248 ]. However, SphK1-mediated IGFBP-3 activated VEGF, which resulted in angiogenesis [ 249 ].…”
Section: Roles Of Mitochondria and Cell Signaling Pathways For S1p-in...mentioning
confidence: 99%